Advances in Indoor Cooking Using Solar Energy with Phase Change Material Storage Systems - Selvaraj Balachandran; Jose Swaminathan (Energies, 2022)
One of the key areas of the UN’s sustainable development goals is growing affordable and clean energy. Utilizing solar energy that is now accessible will significantly lessen the demand for fossil fuels. Around the world, cooking is a crucial activity for homes and uses a lot of non-renewable energy. Uncontrolled firewood usage results in deforestation, whereas using biomass-related fuels in inefficient stoves can result in smoke emanating from the kitchen and associated health issues. The benefits of solar cooking include reducing smoke-related problems and saving on fossil fuels and firewood. Applying thermal storage systems in cooking helps households have all-day cooking. This review article presents the research and development of a solar cooking system that transfers solar energy into the kitchen and integrates with the thermal energy storage system, finding the factors affecting indoor solar cooking performance. Adding portable cooking utensils helps in improved solar indoor cooking. Multiple phase change materials arranged in cascaded to store thermal energy helps in quick heat transfer rate, thus enabling better and faster cooking. A novel indoor solar cooker with an innovative arrangement of evacuated tube-based compound concentrating parabolic (CPC) collectors with a cascaded latent heat thermal energy storage system is proposed and needs to be tested under actual meteorological conditions.